2016
DOI: 10.1002/cncr.30488
|View full text |Cite
|
Sign up to set email alerts
|

Local therapy reduces the risk of liver failure and improves survival in patients with intrahepatic cholangiocarcinoma: A comprehensive analysis of 362 consecutive patients

Abstract: Purpose Treatment methods for intrahepatic cholangiocarcinoma (ICC) have improved, but their impact on outcomes remains unclear. We evaluated the outcomes of patients definitively treated with resection, radiation, and chemotherapy for ICC, stratified by era. Methods Clinicopathologic characteristics, cause of death, disease-specific survival (DSS), and intrahepatic progression-free survival (IPFS) were compared among patients who underwent resection, radiation, or chemotherapy as definitive treatment strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 32 publications
1
49
1
Order By: Relevance
“…ICC is a fatal primary liver carcinoma, which originating from the intrahepatic bile duct epithelium beyond the second-order bile ducts [ 5 ] [ 26 , 27 ]. ICC is the second most common all primary liver cancers in the worldwide, the actual incidence has been increasing steadily and substantially over the past decades and has a poor outcomes and high mortality rate due to the high invasiveness and recurrence [ 1 , 28 30 ]. Some previous studies reported that Wip1 expression was associated with miR-17-5p through activation of the p38 pathway in hepatocellular carcinoma (HCC)[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICC is a fatal primary liver carcinoma, which originating from the intrahepatic bile duct epithelium beyond the second-order bile ducts [ 5 ] [ 26 , 27 ]. ICC is the second most common all primary liver cancers in the worldwide, the actual incidence has been increasing steadily and substantially over the past decades and has a poor outcomes and high mortality rate due to the high invasiveness and recurrence [ 1 , 28 30 ]. Some previous studies reported that Wip1 expression was associated with miR-17-5p through activation of the p38 pathway in hepatocellular carcinoma (HCC)[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A n o t a b l e f e a t u r e o f u n r e s e c t a b l e i n t r a h e p a t i c cholangiocarcinoma is that the majority of patients die of tumor-related liver failure (2); while extrahepatic distant metastasis is prevalent, it is not as frequently the cause of death as the intrahepatic disease. Inadequate control of the primary tumor and satellite lesions can lead to parenchymal loss and liver failure due to vascular compromise (portal venous or hepatic vein obstruction) or biliary obstruction (potentially leading to sepsis) (3). Our review of patients with unresectable intrahepatic cholangiocarcinoma who received radiotherapy at MD Anderson Cancer Center from 2002 to 2014 revealed that a bioequivalent dose less than 80.5 Gy BED led to poor tumor control.…”
Section: The Importance Of Local Controlmentioning
confidence: 95%
“…In this study, we noted improvements over time with resection and radiotherapy, likely owing to technical improvements in these treatments. On multivariable analysis, receipt of local therapy (with resection or definitive radiotherapy) was the sole predictor of death without liver failure (3).…”
Section: The Importance Of Local Controlmentioning
confidence: 99%
“…With technological advances in radiation oncology and ablation technologies, alternative methods are increasingly utilized for local tumor control. This rationale for liverdirected therapies is underscored by data that show survival benefit and decreased risk of liver failure in patients who receive local therapy with resection or definitive radiotherapy (6). To that end, multiple modalities have been heterogeneously employed for local tumor control.…”
Section: Introductionmentioning
confidence: 99%